Cryopreserved mesenchymal stem cells regain functional potency following a 24-h acclimation period - Antebi, Ben (J Transl Med, 2019)
BACKGROUND: Mesenchymal stem cells (MSCs) are attractive cell-therapy candidates. Despite their popularity and promise, there is no uniform method of preparation of MSCs. Typically, cells are cryopreserved in liquid nitrogen, thawed, and subsequently administered to a patient with little to no information on their function post-thaw. We hypothesized that a short acclimation period post-thaw will facilitate the recovery of MSC’s functional potency. METHODS: Human bone-marrow-derived MSCs were divided into 3 groups: FC (fresh cells; from existing culture); TT (thawed + time; acclimated for 24 h post-thaw); and FT (freshly thawed; thawed and immediately used). The 3 groups were analyzed for their cellular and functional potency. RESULTS: Phenotypic analysis demonstrated a decrease in CD44 and CD105 surface markers in FT MSCs, with no change in the other two groups. All MSCs were able to differentiate down the osteogenic and chondrogenic lineages. In FT cells, metabolic activity and apoptosis was significantly increased with concomitant decrease in cell proliferation; clonogenic capacity; and key regenerative genes. Following 24-h acclimation, apoptosis was significantly reduced in TT cells with a concomitant upregulation in angiogenic and anti-inflammatory genes. While all MSCs significantly arrested T-cell proliferation, the TT MSCs were significantly more potent. Similarly, although all MSCs maintained their anti-inflammatory properties, IFN-γ secretion was significantly diminished in FT cells. CONCLUSIONS: These data demonstrate that FT MSCs maintain their multipotent differentiation capacity, immunomodulatory function, and anti-inflammatory properties; yet, various aspects of cell characteristics and function are deleteriously affected by cryopreservation. Importantly, a 24-h acclimation period ‘reactivates’ thawed cells to recover their diminished stem-cell function.